PENGURUSAN PROMOSI PAKAIAN DAN TEKSTIL TRADISIONAL KAUM INDIA: KAJIAN DI GAYATHIRI SILK SAREES PALACE(M) SDN BHD SUNGAI PETANI, KEDAH - PUNITHA, CHANDRAN (Universiti Malaysia Sarawak (UNIMAS), 2016)
This study focuses on the promotion management of Indian traditional clothes and textiles.This study discusses how traditional Indian clothes management of sales took place, the promotional tools used, type of challenges faced by Gayathiri Silk Sarees Palace which prevents to achieve their objectives of promotion and promotion strategies used to increase demand and sales of traditional Indian clothing. This study was done qualitatively to identify the challenges faced by traditional Indian clothing store, emphasize new promotional techniques used and the efforts made to increase demand and sales of textile products and traditional Indian clothing.The results of this study show that Gayathiri Silk Sarees Palace maintains a systematic approach of promotion from planning stage to the implementation of the promotion. The most frequently used promotional mixs are advertising, verbals and exhibitions. There are several strategies applied which showed positive impact on promotion of traditional Indian clothing business Gayathiri Silk Sarees Palace.